1995
DOI: 10.1073/pnas.92.8.3511
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a differentially regulated splicing isoform of human NF-E2.

Abstract: The transcription factor NF-E2 (nuclear factor erythroid 2), interacting via DNA motifs within regulatory regions of several hematopoietic genes, is thought to mediate the enhancer activity of the globin locus control regions. By screening a human fetal liver cDNA library with probes derived from mouse NF-E2, we have isolated a splicing variant of the NF-E2 gene (fNF-E2) that differs in the 5' untranslated region from the previously reported cDNA (aNF-E2). The fNF-E2 isoform is transcribed from an alternative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 28 publications
1
25
1
Order By: Relevance
“…Our mRNA analysis indicated that in normal human MKs the a isoform is much more highly expressed than the f isoform. This finding is also consistent with the preponderance of the a isoform found by Pischedda et al 13 and Moroni et al 51 in adult human BM and the myeloid component of mouse BM, respectively.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Our mRNA analysis indicated that in normal human MKs the a isoform is much more highly expressed than the f isoform. This finding is also consistent with the preponderance of the a isoform found by Pischedda et al 13 and Moroni et al 51 in adult human BM and the myeloid component of mouse BM, respectively.…”
Section: Discussionsupporting
confidence: 81%
“…Although both isoforms are always coexpressed in every human cell type, the f mRNA is more abundant in fetal liver and less abundant in adult bone marrow (BM) compared to the a isoform. 13 Mice lacking p45 NF-E2 show megakaryocytosis and severe thrombocytopenia leading to fatal hemorrhage, and also have mild to moderate anemia. 2 Loss of p45 NF-E2 interferes with MK maturation at an advanced stage: ultrastructural studies reveal a markedly reduced number of granules and failure to form platelet fields.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, our finding of a promoter-like sequence (containing a TATA box) immediately upstream for the 5Ј end of the ⌬LF mRNA suggests that transcription could initiate from two different promoters within the same LF gene and, as a result, specify alternative first exons. This is the situation that occurs with the human NF-E2 gene (49). In this case, use of alternative promoters specifies the major fetal and adult forms of the NF-E2 mRNA.…”
Section: Discussionmentioning
confidence: 99%